The conceptual design and application of web-based tourism decision support systems - Masron, T.; Ismail, N.; Marzuki, A. (Public Administration and Public Services Academy of Economic Studies, 2016)
Decision support system (DSS) can be defined as an interactive computer-based information system which is designed to support and give solutions to decision problems where there is a geographic or spatial component to the decision, with interactive capabilities to improve the understanding of the problem through the use of models and data processing. Web-based DSS is a system that links decision support information or tools to decision-makers through web environment or internet. The Web-based DSS have reduced technological barriers and made it easier and less costly to make decisions that relevant to information available which geographically distributed locations. The study of decision support systems is an applied discipline that uses knowledge and especially theory from other disciplines and one of them is tourism field. Tourism is the interrelated system that includes tourists and the associated services that are provided and utilized (facilities, attractions, transportation and accommodation) to aid in their movement. The paper aims is to discuss the conceptual design and application of web-based tourism decision support system (TDSS) of Langkawi Island.